VD_FINDINFO Jug / 2011 / 133 vom 4. April 2011 - VD Tribunal cantonal (2011)
APPRÉCIATION DES PREUVES, LIBRE APPRÉCIATION DES PREUVES, IN DUBIO PRO REO | 126 CPP (CH), 398 al. 3 let. a CPP (CH), 398 al. 3 let. b CPP (CH)